2017
DOI: 10.1136/oemed-2016-104024
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin promoter variants are associated with increased soluble mesothelin-related peptide levels in asbestos-exposed individuals

Abstract: Soluble-Mesothelin Related Peptide (SMRP) is a promising diagnostic biomarker for malignant pleural mesothelioma (MPM), but various confounders hamper its usefulness in surveillance programs. We previously showed that a single nucleotide polymorphism (SNP) within the 3'untranslated region (3'UTR) of mesothelin (MSLN) gene could affect the levels of SMRP. Here, we focused on SNPs located within MSLN promoter and found a strong association between serum SMRP and variant alleles of rs3764247, rs3764246 (that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Similar results were reported for SNPs in the 5' UTR of the MSLN gene that may affect binding of transcription factors: polymorphic alleles were associated with increased SMRP levels only in subjects without MM and accounting for the genotype improved the diagnostic performance of SMRP. 25,26 These results suggest that cutoff values should be redefined taking into account the MSLN genetic variability to facilitate the interpretation of SMRP measurements. 26 For example, a lower cutoff used in subjects with the wild-type genotype would decrease false negative results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Similar results were reported for SNPs in the 5' UTR of the MSLN gene that may affect binding of transcription factors: polymorphic alleles were associated with increased SMRP levels only in subjects without MM and accounting for the genotype improved the diagnostic performance of SMRP. 25,26 These results suggest that cutoff values should be redefined taking into account the MSLN genetic variability to facilitate the interpretation of SMRP measurements. 26 For example, a lower cutoff used in subjects with the wild-type genotype would decrease false negative results.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 These results suggest that cutoff values should be redefined taking into account the MSLN genetic variability to facilitate the interpretation of SMRP measurements. 26 For example, a lower cutoff used in subjects with the wild-type genotype would decrease false negative results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The diagnostic accuracy of mesothelin has been evaluated in several studies (21,(23)(24)(25) and the systematic review and meta-analysis recently performed showed a high specificity (around 89% and 96%) but a low sensitivity (between 32% and 47%) of mesothelin as a diagnostic marker; thus although SMRPs may help to discriminate the MPM from the non-MPM subjects, the sensitivity of the assay is still inadequate (88). In order to better characterize the sensitivity and specificity of SMRP as a biomarker for MPM it should take in consideration that SMRP performance as diagnostic biomarker could be influenced by genetics variants, as show in the recent work by De Santi et al (30) and SNP located in the promoter or in the 3'UTR of MSLN gene could affect protein expression levels (89). SMRPs diagnostic value has been evaluated also in pleural effusion (25,26,29) and it has been observed a higher diagnostic performance in pleural effusion than in serum assessment (22).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%